ANALISIS PERENCANAAN PAJAK PENGHASILAN PPH BADAN SEBAGAI UPAYA MENGEFISIENSIKAN BEBAN PAJAK PADA PT MANREPO TAMBANG REMPOA. - Bakri, Asri Ady; Salim, Mursalam (Restitusi : Jurnal Riset Perpajakan, 2022)
Study is to analyze the application of corporate income tax planning in an effort to streamline the tax burden at PT Manrepo Tambang Rempoa. In conducting this research, the writer uses a comparative descriptive method which uses qualitative and quantitative data types, while the data collection techniques used are observation, documentation and interviews. From the results of the study indicate that from the calculation before and after tax planning, the efficiency level of the income tax burden experienced savings. This occurred due to the addition of costs that could reduce the company's fiscal profit so that from the results of the comparative analysis of the tax burden before and after tax planning, the company obtained tax savings of Rp.2.136.301